Following Bradshaw and Bishop into Jacob's Room: British and Canadian editing strategies (tunnelling the textual hotspots, minding the gaps). Issue 1 (2nd January 2020) - Goldman, Jane
ABSTRACT: The pioneering editorial practices of Canadian Professor Edward Bishop and the late Professor David Bradshaw offer distinct but complementary approaches to annotating Woolf's Jacob's Room (1922). Bishop, editors of the Shakespeare Head edition of the novel and of a transcription of the holograph draft, has gifted new modernist editing the hugely influential, crucial instruction "Mind the gap!, " urging close attention to Woolf's spacing and lay-out of the material page as important literary signifiers. "Mind the word!" might well be the riposte of Bradshaw (1955–2016) who has left a body of scholarship pressing for close critical attention to every passing cultural, material reference, not least in the numerous proper names of people, places, etc., populating this highly allusive, densely palimpsestic text. Building on Bradshaw's critical technique and research into the onomastics and Bishop's editorial insights into the spaces and gaps in Jacob's Room, this essay explores some of my findings whilst working as an editor and annotator of the work for the forthcoming Cambridge UP edition. "tunnelling, " as Woolf herself called it, into the signifying networks behind her writing, to consider questions of paternity, war and national identity that hang over Jacob's Room: "'Did you ever hear who his father was?'"